STRATEGI PENGEMBANGAN PROGRAM PERTANIAN TANAMAN PANGAN DI DISTRIK SEMANGGA KABUPATEN MERAUKE - Untari Untari (Universitas Musamus, Merauke, Papua, 2012)
Local government created programs to develop the agricultural sector. The region which experienced increase rice production is Tanah Miring District (32.041 tons), Kurik (29.601 ton), and Semangga District (20.231 ton). This research is aim to analyzed levels of achievement for the programs to improving the agriculture productivity and formulating the strategies for the best agriculture productivity in Semangga District. The research used descriptive analytics method. This study consist the primary and secondary data with 89 sample respondents. Data were collected from this study will analyzed wih GEP analysis. The result was showed that farmer as a subject of agriculture should be involved to arrange the programs. There are many program from the government to improve rice production such as direct aid seed preeminent (Bantuan Langsung Benih Unggul/BLBU), field integrated management of the plant school (Sekolah Lapangan Pengelolaan Tanaman Terpadu/SL-PTT), tools and machinery agriculture programe (program alat dan mesin pertanian), land optimization programe (optimalisasi lahan) and organic fertilizer management unit (unit pengelolaan pupuk organik). Those programe was funded by the government from APBN, Otsus, and DAK